Longer legs are associated with greater risk of incident venous thromboembolism independent of total body height - Lutsey, Pamela L.; Cushman, Mary; Heckbert, Susan R.; Tang, Weihong; Folsom, Aaron R. (Thrombosis and Haemostasis, 2011)
Several studies have reported that taller individuals are at greater risk of venous thromboembolism (VTE). We hypothesised that longer leg length would be positively associated with incident VTE, and would explain the height association. LITE ascertained VTE in a prospective population-based sample of 21,860 individuals aged 45 and older. Leg length was measured as standing height minus torso length. Cox regression models were adjusted for age, race, sex, waist circumference, diabetes, and factor VIII. To evaluate whether leg length was associated with VTE risk independent of height, we standardised leg length and height per 1 standard deviation (SD), and then included them simultaneously in Cox regression models. A total of 641 incident VTE cases accrued over a median follow-up of 16 years. Participants in the highestquintile of leg length were at 59% (95% CI: 22%-108%) greater risk of VTE, relative to the lowest quintile. For height, risk was 45% (12%-88%) greater for those in the highest quintile, compared to the lowest. When leg length and height were modelled simultaneously leg length remained associated with VTE risk (HR per 1 SD: 1.21 (1.04–1.40) while height was unrelated (HR per 1 SD: 1.00 (0.86–1.16). To conclude, participants with longer legs were at greater risk of incident VTE, and leg length explained the relation of height to VTE. It remains to be established whether this finding is due to greater venous surface area, a larger number of venous valves, or greater hydrostatic pressure among individuals with longer legs.
Keywords: Height; leg length; venous thromboembolism; Atherosclerosis Risk in Communities Study (ARIC); Cardiovascular Health Study (CHS)